2009
DOI: 10.2165/11200860-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Asenapine

Abstract: Asenapine is a novel psychopharmacological agent that binds with high affinity and specificity to numerous dopamine, serotonin, noradrenaline (norepinephrine) and histamine receptor subtypes. It is being developed for the treatment of schizophrenia and bipolar mania. In two randomized, controlled trials of asenapine monotherapy and in one randomized, controlled trial of adjunctive asenapine therapy in adult patients with bipolar I disorder, sublingual asenapine produced significantly greater reductions from ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…Of these, only one was a clinical trial report (6), the remainder included a post hoc evaluation of dropouts in six placebo-controlled short-term trials (7), a paper describing clinical trial design and rationale for the treatment of negative symptoms (8), a positron emission tomography (PET) study in healthy subjects (9), 31 papers describing preclinical laboratory and animal experiments and 12 reviews of which only one focused exclusively on asenapine (10). Query of http://www.fda.gov resulted in the acquisition of two principal documents, a briefing book for the FDA Psychopharmacologic Drugs Advisory Committee prepared by FDA staff (5) and a briefing document prepared by Schering-Plough Corporation (11).…”
Section: Study Selectionmentioning
confidence: 99%
“…Of these, only one was a clinical trial report (6), the remainder included a post hoc evaluation of dropouts in six placebo-controlled short-term trials (7), a paper describing clinical trial design and rationale for the treatment of negative symptoms (8), a positron emission tomography (PET) study in healthy subjects (9), 31 papers describing preclinical laboratory and animal experiments and 12 reviews of which only one focused exclusively on asenapine (10). Query of http://www.fda.gov resulted in the acquisition of two principal documents, a briefing book for the FDA Psychopharmacologic Drugs Advisory Committee prepared by FDA staff (5) and a briefing document prepared by Schering-Plough Corporation (11).…”
Section: Study Selectionmentioning
confidence: 99%
“…Partial agonist activity at 5-HT 1A receptors was confirmed by the blockade of inhibitory effect of asenapine on neuronal firing in the dorsal raphe nucleus and hippocampus by the 5-HT 1A receptor antagonist WAY100635 (Ghanbari et al 2009). Studies in behavioural animal models have shown the antipsychotic and procognitive effects of asenapine Marston et al 2009;Frånberg et al 2008), which have now been clinically validated in the treatment of acute schizophrenia (Kane et al 2010;Potkin et al 2007;Weber and McCormack 2009). Although there are some preliminary data to suggest that asenapine improves cognitive deficits in schizophrenia patients (Fleming et al 2007), this requires further validation.…”
Section: E H + V E H P C P ( P ) + V E H P + ( a ) P + A + S C H P +mentioning
confidence: 99%
“…A recent review cited data showing a benefit of asenapine on persistent, prominent negative symptoms using the NSA-16 as a detailed measure of negative symptoms [17].…”
Section: Asenapinementioning
confidence: 99%